Metal graphene composite material and preparation method thereof

By using a mixed molten salt of KCl and NaCl and reacting with boron carbide with metal, a metal graphene composite material with uniform graphene distribution, high content and high purity was prepared, which solved the problems of high cost, poor consistency and low content in the prior art.

CN119710350AActive Publication Date: 2025-03-28CHAOWEI POWER GROUP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411962256.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing preparation methods for metal graphene composite materials have problems such as high cost, poor alloy consistency, uneven graphene dispersion, low graphene content and low purity.

Method used

The mixed molten salt of KCl and NaCl is mixed with boron carbide, heated and melted by heating and stirring device, and left to stand to form a mixture of molten salts of upper and lower layers. The lower layer material is a metal graphene composite material.

Benefits of technology

The content and purity of graphene in the composite material are improved, uniformity and consistency are good, production costs are reduced, and the formation of metal oxides is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710350A_ABST
    Figure CN119710350A_ABST
Patent Text Reader

Abstract

The invention relates to a metal graphene composite material and a preparation method thereof, belongs to the technical field of graphene composite materials, and aims to solve the problems of high production cost, poor alloy consistency, non-uniform graphene dispersion, low graphene content, low metal graphene composite material purity and the like of the metal graphene composite material prepared by the existing method. According to the method disclosed by the invention, KCl and NaCl are melted and then cooled, and boron carbide is added, so that the salt can be sufficiently dehydrated, the melting point of the melted mixed salt is reduced, the temperature required for secondary melting is lower, the temperature is more beneficial to the proceeding of the reaction, and the content of graphene in the composite material is further increased; meanwhile, the size and the number of layers of the graphene are reduced, and the purity of the composite material is improved. The metal graphene composite material prepared through the method is uniform in graphene distribution, high in graphene content and high in purity, the preparation method is simple, the preparation time is short, the production cost is low, mechanical stirring is not used, and molten salt can be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of graphene composite materials, and in particular to a metal graphene composite material and a preparation method thereof. Background Art

[0002] Graphene is one of the strongest materials known. It also has good toughness and can be bent. The theoretical Young's modulus of graphene is 1.0 TPa and the inherent tensile strength is 130 GPa. The carrier mobility of graphene at room temperature is about 15000 cm 2 / (V·s), which is more than 10 times that of silicon and more than twice that of indium antimonide (InSb), the material with the highest known carrier mobility. Under certain specific conditions, such as low temperature, the carrier mobility of graphene can even reach 250,000 cm 2 / (V·s). Unlike many materials, the electron mobility of graphene is less affected by temperature changes. At any temperature between 50 and 500K, the electron mobility of a single layer of graphene is 15000cm 2 / (V·s) approximately.

[0003] By combining new materials such as graphene with traditional metal materials, traditional metal materials can demonstrate excellent performance, including electrical, mechanical, thermodynamic and other aspects. At present, these materials have been highly recognized and applied in technology and the market. For example, metal graphene composite materials have broad application prospects in aviation, aerospace, satellites, communications and semiconductors.

[0004] However, the current preparation methods of metal graphene composites have problems such as high cost, poor alloy consistency, uneven graphene dispersion, low graphene content, and low purity. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide a metal graphene composite material and a preparation method thereof, so as to solve at least one of the problems of the metal graphene composite material prepared by the existing method, such as high production cost, poor alloy consistency, uneven graphene dispersion, low graphene content, and low purity of the metal graphene composite material.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a method for preparing a metal graphene composite material, comprising the following steps:

[0008] (1) melting KCl and NaCl to obtain a mixed molten salt, cooling and crushing to obtain a mixed salt, and mixing the mixed salt with boron carbide to obtain a mixture;

[0009] (2) adding the mixture to a metal, loading the mixture into a graphite crucible, placing the mixture in a heating and stirring device, heating the mixture to melt, and allowing the mixture to stand to obtain a molten salt mixture having two layers, the lower layer material being the metal-graphene composite material.

[0010] Furthermore, in step (1), the molar ratio of KCl to NaCl is 1:2 to 4:2, preferably 2:3 to 3:2.

[0011] Furthermore, in step (1), the melting temperature is 800-900° C., and the melting and dehydration time is 30-60 min.

[0012] Furthermore, in step (1), the mass ratio of the total mass of KCl and NaCl to the mass of boron carbide is 1:0.04-0.1, preferably, 1:0.05-0.1.

[0013] Furthermore, in step (2), the metal is lead or aluminum.

[0014] Furthermore, in step (2), the mass ratio of the total mass of KCl and NaCl to the metal is 1:3.0 to 3.6, preferably, 1:3.0 to 3.5.

[0015] Furthermore, in step (2), the heating and melting temperature is 700-800° C., and the time is 0.5-2 h.

[0016] Furthermore, the method further comprises pouring the upper and lower layers of the molten salt mixture into a metal mold to obtain the metal-graphene composite material.

[0017] Furthermore, the metal mold needs to be preheated at a temperature of 150-200° C. for 1-2 hours.

[0018] Furthermore, the metal is at least one of lead, aluminum or zinc.

[0019] In a second aspect, the present invention provides a metal graphene composite material prepared by the above method.

[0020] In a third aspect, the present invention provides an application of the above-mentioned metal graphene composite material in aviation, aerospace, satellite, communication or semiconductor materials.

[0021] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0022] (1) The method of the present invention melts KCl and NaCl, cools them, and adds boron carbide, so that the salt can be fully dehydrated, the melting point of the melted mixed salt is reduced, and the temperature required for the second melting is lower, which is more conducive to the reaction, further increasing the content of graphene in the composite material; it is also beneficial to reduce the size and number of graphene layers, and improve the purity of the composite material. Secondly, the molten salt mixture is placed on the upper layer of the metal object to reduce the formation of metal oxides. All materials are added in a cold state, which can avoid the temperature difference series risks of the prior art of first melting the metal and then adding the molten salt. The mixed state of the molten salt material and the carbonizer makes the eutectic better and the utilization rate higher;

[0023] (2) The metal graphene composite material prepared by the method of the present invention has good uniformity of graphene distribution, high graphene content, graphene content ≥0.006%, high purity, purity ≥99.92%, hardness ≥4.6HB, simple preparation method, short preparation time, low production cost, no mechanical stirring, and the molten salt can be reused.

[0024] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0026] Figure 1 This is a SEM image of the composite material prepared in Example 1 of the present invention;

[0027] Figure 2 This is a BES diagram of the composite material prepared in Example 1 of the present invention;

[0028] Figure 3 This is the Raman spectrum of the metal graphene composite material prepared in Example 1 of the present invention.

[0029] Reference numerals:

[0030] 1-Graphene membrane. DETAILED DESCRIPTION

[0031] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0032] A specific embodiment of the present invention discloses a method for preparing a metal graphene composite material, comprising the following steps:

[0033] (1) melting KCl and NaCl to obtain a mixed molten salt, cooling and crushing to obtain a mixed salt, and mixing the mixed salt with boron carbide to obtain a mixture;

[0034] (2) adding the mixture to a metal, loading the mixture into a graphite crucible, placing the mixture in a heating and stirring device, heating the mixture to melt, and allowing the mixture to stand to obtain a molten salt mixture having two layers, the lower layer material being the metal-graphene composite material.

[0035] The method of the present invention melts KCl and NaCl, cools them, and adds boron carbide, so that the salt can be fully dehydrated, the melting point of the melted mixed salt is reduced, and the temperature required for secondary melting is lower, which is more conducive to the reaction, and further improves the content of graphene in the composite material; it is also conducive to reducing the size and number of graphene layers, and improving the purity of the composite material. Secondly, the molten salt mixture is placed on the upper layer of the metal object, which can reduce the formation of metal oxides. All materials are added in a cold state, which can avoid the temperature difference series risks of the prior art of first melting the metal and then adding the molten salt. The mixed form of the molten salt material and the carbonizing agent makes the eutectic better and the utilization rate higher.

[0036] The metal graphene composite material prepared by the method of the present invention has uniform graphene distribution, high graphene content, high purity, simple preparation method, short preparation time, low production cost, no mechanical stirring is used, and the molten salt can be reused.

[0037] The carbon source in the method of the present invention comes from boron carbide. Boron carbide decomposes under specific conditions to form carbon atoms, which enter into the lead liquid and reorganize to form a graphene structure after reaching a certain concentration. Therefore, the composite material prepared by the method of the present invention has better bonding between graphene and lead and more uniform dispersion. Secondly, graphene is expensive. Compared with the method of directly adding graphene, the method of the present invention has a cost advantage.

[0038] In a specific embodiment, in step (1), the molar ratio of KCl to NaCl is 1:2 to 4:2, for example, 1:2, 2:3, 5:6, 1:1, 7:6, 4:3, 3:2, 4:2.

[0039] In a specific embodiment, in step (1), the molar ratio of KCl to NaCl is 2:3 to 3:2, for example, 2:3, 5:6, 1:1, 7:6, 4:3, 3:2.

[0040] The purpose of using NaCl and KCl as the mixed salt in the present invention is that the mixed salt has a lower melting point than a single salt. Within the above-mentioned molar ratio range, the melting point is relatively low near the eutectic point of NaCl and KCl.

[0041] In a specific embodiment, in step (1), the melting temperature is 800-900°C, for example, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, and the melting and dehydration time is 30-60 min, for example, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min.

[0042] Within the above melting temperature and time, NaCl and KCl can be fully melted with low energy consumption and will not affect the service life of the equipment.

[0043] In a specific embodiment, in step (1), the crushed particle size is less than 3 mm, which is conducive to uniform mixing with boron carbide.

[0044] In a specific embodiment, in step (1), the mass ratio of the total mass of KCl and NaCl to the mass ratio of boron carbide is 1:0.04-0.1, preferably, 1:0.05-0.1, for example, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1. Since boron carbide is a carbon source, it must be in excess to ensure sufficient graphene content in the product.

[0045] In a specific embodiment, in step (2), the metal is at least one of lead, aluminum or zinc.

[0046] In a specific embodiment, in step (2), the mass ratio of the total mass of KCl and NaCl to the metal is 1:3.0-3.6, preferably, 1:3.0-3.5, for example, 1:3.0, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5.

[0047] In a specific embodiment, in step (2), the heating and melting temperature is 700-800°C, for example, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, and the time is 0.5-2h, for example, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h.

[0048] Preferably, the heating and stirring device described in the present invention is an induction furnace, and the metal graphene composite material described in the present invention is made in an induction furnace. In the induction furnace, due to the electric power, the convection of the metal melt is ensured and the mixing of the metal melt is achieved. The reaction is carried out by an induction furnace, which can reduce the impurities introduced by stirring, the stirring step can be omitted, and the operation is simplified. In addition, the induction furnace heats up quickly, which can shorten the heating and melting time. Molten salt is not conductive, so it can only heat the molten metal and will not move under the action of electromagnetic force. Convection in molten salt is essentially just heat flow. The salt heated by the metal rises from the molten metal-salt interface to the salt-furnace atmosphere interface and is replaced by a colder salt, which ensures the continuous movement of the molten metal-salt interface. This is because boron carbide and salt are mixed together, the salt at the metal-salt interface moves upward under the action of heat flow, the colder salt at the top sinks, and the boron carbide also accompanies the same movement, and the material at the metal-salt interface is always changing, thereby playing a stirring role, and no additional mechanical stirring is required.

[0049] In a specific embodiment, the method further comprises pouring the upper and lower layers of the molten salt mixture into a mold to obtain the metal graphene composite material.

[0050] Specifically, the mold needs to be preheated at a temperature of 150-200°C (for example, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C) for 1-2h, for example, 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h.

[0051] It should be noted that the mold is preheated in a low-temperature resistance furnace, and the low-density molten salt floats in the form of slag, and can be easily separated from the ingot after being taken out of the mold. The separated molten salt can be used in step (1).

[0052] In the present invention, the purity of pure lead is 99.99%, the purity of KCl is 99.8%, the purity of NaCl is 99.8%, the purity of boron carbide is ≥96.0%, and the particle size of boron carbide is at least F220.

[0053] Specifically, the metal is at least one of lead, aluminum or zinc.

[0054] Another specific embodiment of the present invention discloses a metal graphene composite material prepared by the above method.

[0055] In the metal graphene composite material prepared by the method of the present invention, graphene is uniformly dispersed in the metal graphene composite material in the form of a transparent film, the size of the transparent film is about (5-20)×(20-40) μm, and the graphene is preferably double-layer graphene.

[0056] The graphene content in the metal graphene composite material prepared by the method of the invention is 0.005-0.01% and the purity is ≥99.95%.

[0057] Another specific embodiment of the present invention discloses an application of the above-mentioned metal graphene composite material in aviation, aerospace, satellite, communication or semiconductor materials.

[0058] The technical solution of the present invention is further explained below in conjunction with specific embodiments.

[0059] In the following examples, the purity of pure lead and aluminum is 99.99%, the purity of KCl is 99.8%, the purity of NaCl is 99.8%, the purity of boron carbide is 96.0%, and the particle size of boron carbide is F220.

[0060] Example 1

[0061] A method for preparing a metal-graphene composite material comprises the following steps:

[0062] (1) KCl and NaCl were mixed in a molar ratio of 1:1 (total mass of 150 g), placed in a graphite crucible in a Graficarbo resistance furnace, melted and dehydrated at 850° C. for 40 min, cooled, crushed to a particle size of less than 3 mm, and 12.5 g of boron carbide was added to obtain a mixture;

[0063] (2) 500 g of lead was mixed with the mixture, loaded into a crucible made of high-density graphite, placed in a YiHui M.MF.00004 induction furnace, heated and melted at a temperature of 750° C. for 1 hour to obtain a molten salt mixture, and the molten salt mixture was poured into a metal mold, wherein the metal mold was preheated to 200° C. for 1 hour in a low-temperature resistance furnace SNOL 58 / 350, and the low-density molten salt floated in a slag state, and after being taken out of the mold, it was easily separated from the metal graphene composite material.

[0064] The carbon modification of the composite material prepared in this example was checked using a Renishaw INVIA0820-04 confocal Raman scattering spectrometer, and it was found that the carbon modification was graphene. Figure 1 and 2 As shown, the graphene film 1 is transparent and has a size of about 20×40 μm. Figure 1 and 2 It can be seen that in the graphene composite material prepared by the method of the present invention, the graphene film is small in size and evenly dispersed, without agglomeration or agglomeration.

[0065] The Raman spectrum of the metal graphene composite material prepared in this example is as follows: Figure 3 As shown. From the ratio of the intensity of the 2D peak and the G peak, I2D / IG, which is equal to 0.61, it can be seen that a double-layer graphene is formed. Due to the interaction between the two layers, it is stronger than a single layer, has better mechanical strength and higher fracture toughness. The two layers support each other and will not have brittle fractures like a single layer when subjected to force. Its thermal conductivity and electrical conductivity are also good, and its stability is higher than a single layer. The low defectivity of graphene is proved by the intensity of the peak D that characterizes the defectivity of the carbon film and the fact that the ratio of the peak D to G, ID / IG, is 0.42. It can be judged that graphene has entered the composite material and the graphene is a double-layer structure.

[0066] Example 2

[0067] A method for preparing a metal-graphene composite material comprises the following steps:

[0068] (1) KCl and NaCl were mixed in a molar ratio of 3:2, placed in a graphite crucible in a Graficarbo resistance furnace, melted and dehydrated at 800° C. for 60 min, cooled, and crushed to a particle size of less than 3 mm, and boron carbide was added, with the total mass ratio of KCl and NaCl to boron carbide being 1:0.05 to obtain a mixture;

[0069] (2) Lead is mixed with the mixture, the mass ratio of the total mass of KCl and NaCl to lead is 1:3.0, and the mixture is placed in a crucible made of high-density graphite, placed in a YiHui M.MF.00004 induction furnace, and heated to melt at a temperature of 700°C for 2 hours to obtain a molten salt mixture, and the molten salt mixture is poured into a metal mold, wherein the metal mold is preheated to 150°C in a low-temperature resistance furnace SNOL 58 / 350 for 2 hours, and the low-density molten salt floats in a slag state, and after being taken out of the mold, it is easily separated from the metal graphene composite material.

[0070] The properties of the composite material prepared in this embodiment were tested as in Example 1, and the results were basically the same. Due to limited space, they are not listed one by one.

[0071] Example 3

[0072] A method for preparing a metal-graphene composite material comprises the following steps:

[0073] (1) KCl and NaCl were mixed in a molar ratio of 2:3, placed in a graphite crucible in a Graficarbo resistance furnace, melted and dehydrated at 900° C. for 30 min, cooled, and crushed to a particle size of less than 3 mm, and boron carbide was added, with the total mass ratio of KCl and NaCl to boron carbide being 1:0.1 to obtain a mixture;

[0074] (2) Lead is mixed with the mixture, the mass ratio of the total mass of KCl and NaCl to lead is 1:3.5, and the mixture is placed in a crucible made of high-density graphite, placed in a YiHui M.MF.00004 induction furnace, and heated to melt at a temperature of 800° C. for 0.5 h to obtain a molten salt mixture, and the molten salt mixture is poured into a metal mold, wherein the metal mold is preheated to 200° C. for 1 h in a low-temperature resistance furnace SNOL 58 / 350, and the low-density molten salt floats in a slag state, and after being taken out of the mold, it is easily separated from the metal graphene composite material.

[0075] The properties of the composite material prepared in this embodiment were tested as in Example 1, and the results were basically the same. Due to limited space, they are not listed one by one.

[0076] Example 4

[0077] A method for preparing a metal graphene composite material is the same as that in Example 1, except that in step (2), lead is replaced by aluminum to finally obtain an aluminum graphene composite material.

[0078] Example 5

[0079] The method for preparing a metal-graphene composite material of this embodiment is the same as that of Embodiment 1, except that in step (1), the molar ratio of KCl to NaCl is 1:2.

[0080] Example 6

[0081] The method for preparing a metal graphene composite material of this embodiment is the same as that of Embodiment 1, except that in step (1), the mass ratio of the total mass of KCl and NaCl to the mass of boron carbide is 1:0.04.

[0082] Example 7

[0083] The method for preparing a metal graphene composite material of this embodiment is the same as that of Embodiment 1, except that in step (2), the mass ratio of the total mass of KCl and NaCl to the mass of lead is 1:3.6.

[0084] Comparative Example 1

[0085] The preparation method of a metal graphene composite material in this comparative example is the same as that in Example 1, except that in step (1), KCl, NaCl and boron carbide are directly mixed without melting, cooling and pulverizing KCl and NaCl.

[0086] Comparative Example 2

[0087] The preparation method of a metal graphene composite material in this comparative example is the same as that in Example 1, except that in step (2), the heating and melting temperature is 850° C. and the time is 2.2 h.

[0088] Comparative Example 3

[0089] The preparation method of a metal graphene composite material in this comparative example is the same as that in Example 1, except that in step (2), an open furnace is used for melting in a mechanical stirrer instead of an induction furnace for heating.

[0090] Test Example 1

[0091] The purity, graphene content and number of layers of the composite materials prepared in Examples 1-7 and Comparative Examples 1-3 were tested respectively, and the hardness of the composite materials was tested using a VERZUS 750CCD hardness tester. The results are shown in Table 1.

[0092] Table 1

[0093]

[0094] Compared with Example 1, Comparative Example 1 cancels the raw material pretreatment step, the graphene content in the composite material is significantly reduced, the purity and hardness are also reduced to a certain extent, and the number of graphene layers is increased to 3 layers.

[0095] Compared with Example 1, the graphene content in the prepared composite materials of Examples 5-7 is reduced, and the purity and hardness are also reduced to a certain extent. In Example 5, the number of graphene layers is increased to 3 layers.

[0096] Comparative Example 2 Compared with Example 1, the graphene content in the composite material prepared at a temperature other than that of the present invention is significantly reduced, the purity and hardness are also reduced to a certain extent, and the number of graphene layers is increased to 4 layers.

[0097] Compared with Example 1, the graphene content in the composite material prepared by the induction furnace heating melt method not designed by the present invention is not much different, but the open furnace heats up slowly, and mechanical stirring makes the production process more complicated and may introduce a certain amount of impurities, thereby reducing the purity of the composite material.

[0098] Test Example 2

[0099] Samples were taken from different positions of the graphene composite material obtained in Example 1 to test the carbon content. The obtained data are shown in Table 2.

[0100] Table 2 Test data of carbon content at different positions of graphene composite materials

[0101] Position number Carbon content (%) 1 0.0087 2 0.0091 3 0.0089 4 0.0088 5 0.0090 6 0.0091 7 0.0089 8 0.0092

[0102] It can be seen from the above table that the carbon content in the graphene composite materials at different positions is not much different, indicating that the composite materials prepared by the method of the present invention have good consistency.

[0103] The inventors conducted the above test on the composite materials prepared in other embodiments, and the results were basically the same. Due to limited space, they are not listed one by one.

[0104] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing a metal graphene composite material, characterized in that: The steps include: (1) melting KCl and NaCl to obtain a mixed molten salt, cooling and crushing to obtain a mixed salt, and mixing the mixed salt with boron carbide to obtain a mixture; (2) adding the mixture to metal, placing it in a heating and stirring device, heating to melt, and standing to obtain a molten salt mixture of upper and lower layers, wherein the lower layer material is the metal graphene composite material.

2. The method for preparing a metal graphene composite material according to claim 1, characterized in that: In step (1), the molar ratio of KCl to NaCl is 1:2 to 4:

2.

3. The method for preparing a metal-graphene composite material according to claim 1, characterized in that: In step (1), the melting temperature is 800-900° C., and the melting and dehydration time is 30-60 min.

4. A method for preparing a metal-graphene composite material according to any one of claims 1 to 3, characterized in that: In step (1), the mass ratio of the total mass of KCl and NaCl to the mass of boron carbide is 1:0.04-0.

1.

5. The method for preparing a metal-graphene composite material according to claim 1, characterized in that: In step (2), the metal is at least one of lead, aluminum or zinc.

6. The method for preparing a metal-graphene composite material according to claim 5, characterized in that: In step (2), the mass ratio of the total mass of KCl and NaCl to the metal is 1:3.0-3.

6.

7. A method for preparing a metal-graphene composite material according to any one of claims 1 to 3, characterized in that: In step (2), the heating and melting temperature is 700-800° C. and the time is 0.5-2 h.

8. The method for preparing a metal-graphene composite material according to claim 1, characterized in that: The method further comprises pouring the upper and lower layers of the molten salt mixture into a mold to obtain the metal-graphene composite material.

9. A metal-graphene composite material prepared by the method according to any one of claims 1 to 8.

10. Use of the metal graphene composite material according to claim 9 in aviation, aerospace, satellite, communication or semiconductor materials.

Citation Information

Patent Citations

  • Preparation method for boron-doped graphene

    CN106435632A

  • Method for preparing compact ultrafine-grain boron carbide ceramic material with reduced sintering temperature

    CN106854080A

  • Preparation method of in-situ synthetic graphene reinforced aluminum matrix composite material

    CN110172608A

  • Positive grid alloy containing graphene and preparation method and application thereof

    CN113579210A

  • Eco-friendly functional finish composition using graphene and surface protection and strengthening finishing method of concrete and steel structure using the same

    KR102168827B1